The enlightened minds of the pastoral land of Mărginimea Sibiului - PIȚ, Teodora Maria (Studia Universitatis Babeș-Bolyai Digitalia, 2021)
This project aims to configure a map of the most important personalities in the Mărginimea Sibiului. The present research presents practically the methodology of all the stages completed. Starting with the selection of information, its organization in tables and up to the geographical representation of the information gathered about intellectuals. The career path of each one is not a complex one, but the idea started from the fact that we wanted to demonstrate how a rural, agrarian area, restricted from a geographical point of view, offered to the national culture several paramount intellectuals such as Ioan Lupaș, Octavian Goga, Emil Cioran, Samuel Micu.